OPTIMIZATION OF THE REINFORCEMENT TEXTURE OF A CYLINDRICAL COMPOSITE SHELL UNDER STATIC LOADS - OLODO, ESSE TIMOTHEE EMMANUEL; ADJOVI, CLEMENCIA EDMOND; SHAMBINA, SVETLANA (My University, 2018)
This work is devoted to a method of optimization of the composite shell woven reinforcements. This method is based on Goldenblat-Kopnov’s anisotropic model which is suitable for this material. This study involves three steps: Firstly, it is carried out experimental characterization of the strength properties of the material; then it is proposed a method of optimization of the winding angle of composite shell woven reinforcements based on the strength anisotropy of the material. The third step consist in establishing the variation ranges of the static strength tensor components of this material in three planes of symmetry from the Sylvester’s criterion of positive definition of symmetric matrices. Obtained results allow improve the structural performance of composite shells with woven reinforcements.
Keywords: optimization; Winding angle; texture; variation ranges